Next-generation genetic sexing strain establishment in the agricultural pest Ceratitis capitata - Serafima Davydova; Junru Liu; Nikolay P. Kandul; W. Evan Braswell; Omar S. Akbari; Angela Meccariello (Scientific Reports, 2023)
Abstract Tephritid fruit fly pests pose an increasing threat to the agricultural industry due to their global dispersion and a highly invasive nature. Here we showcase the feasibility of an early-detection SEPARATOR sex sorting approach through using the non-model Tephritid pest, Ceratitis capitata. This system relies on female-only fluorescent marker expression, accomplished through the use of a sex-specific intron of the highly-conserved transformer gene from C. capitata and Anastrepha ludens. The herein characterized strains have 100% desired phenotype outcomes, allowing accurate male–female separation during early development. Overall, we describe an antibiotic and temperature-independent sex-sorting system in C. capitata, which, moving forward, may be implemented in other non-model Tephritid pest species. This strategy can facilitate the establishment of genetic sexing systems with endogenous elements exclusively, which, on a wider scale, can improve pest population control strategies like sterile insect technique.